The Importance Of Video As Learning Media According To Principle Of Media Production “Visuals” - Heru Chakra Setiawan; Widyo Nugroho; Habib Abdur Rofi (Interdiciplinary Journal and Hummanity (INJURITY), 2022)
Video is an electronic medium that capable of combining audio technology and visually together. This research aim to video as learning media as media production of visual. The selection of video can also be packaged in various forms, for example combining face-to-face with group communication, using text, audio and music. Therefore, the educator must be efficiently master how to product the video as learning media, the principle of media production using VISUALS (Visible, Interesting, Simple, Useful, Accurate, Legitimate, Structured) is used to produce a video, as the result, the video media which is the product of VISUAL, This principle helps educators to better understand the essence of making video by paying attention to the visibility side, so that, it can be viewed by many levels of student, as well as attracting the attention of students, simple videos while still providing significant understanding to students, accurate in delivering material, and also remind video educators to pay attention in terms of structure so that the resulting video product is a video that can take the attention of students to the fullest. This paper is a qualitative type with library research whereas the main data is obtained from various journal articles with a content analysis approach.